Análisis iconográfico de la caricatura política de Xavier Bonilla (Bonil) en el gobierno del presidente Rafael Correa Delgado - Bonilla Gallardo, Evelyn Dayana (2013)
The present work shows an abstraction about the possible achievements that can be constructed by applying the iconographic method in the interpretation of the political cartoon Xavier Bonilla (BONIL). The most ambitious goal of this work aims to create a simple proposal for reading the political cartoon, coupling each item is described as iconographic method process described in chapter two. In the first part of the study determines the conceptual foundations of the cartoon, its elements, the formal and visual techniques are described below Iconographic method bases developed by Erwin Panofsky. And reflecting on their possible application in the interpretation of political cartoons, this will design three templates that correspond to the times of iconographic method described in section 2.1.2 of this chapter, in order to facilitate their interpretation and application. In the third chapter provides an approximation of the political cartoon as a journalistic genre, high lighting their qualities. The graphical or symbolic content, contents and function humorous media. We carried out a methodological approach in order to propose a simple tool for the interpretation of political cartooning in general.